2009
DOI: 10.1128/jvi.01084-09
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Restriction Targeting Viral Capsids Perturbs Human Immunodeficiency Virus Type 1 Infection of Nondividing Cells

Abstract: The ability of human immunodeficiency virus (HIV) to infect nondividing cells is a fundamental property by which HIV replicates in critical target cells, such as macrophages and resting CD4+ T cells. Recent studies have revealed that the capsid (CA) protein is a dominant factor that determines retrovirus infectivity in nondividing cells, and several mutations in HIV type 1 (HIV-1) CA abrogate the ability of HIV-1 to infect nondividing cells. We present evidence for a connection between cellular restriction aga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
31
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 50 publications
2
31
0
1
Order By: Relevance
“…1H), suggesting that N121K is inhibited by CypA in the cytoplasm of the target cells as previously observed for other CsA-dependent mutant viruses (5,18). Aphidicolin-induced growth arrest markedly increased the level of N121K inhibition in HeLa cells (as was observed in A92E mutants) (16,17).…”
supporting
confidence: 75%
See 1 more Smart Citation
“…1H), suggesting that N121K is inhibited by CypA in the cytoplasm of the target cells as previously observed for other CsA-dependent mutant viruses (5,18). Aphidicolin-induced growth arrest markedly increased the level of N121K inhibition in HeLa cells (as was observed in A92E mutants) (16,17).…”
supporting
confidence: 75%
“…Viral replication was then examined in Jurkat and H9 cells, and infection efficiency was examined in Jurkat, 293T, and HeLa cells. Figure 1A Previous studies show that CypA-dependent inhibition of infection by some CA mutants is greater in nondividing cells (16,17). Therefore, to investigate whether the mechanism underlying the CypA-dependent inhibition of infection by N121K mutants is similar to that observed for other CA mutants such as A92E, we tested whether cell growth arrest of CypA-or nontarget short hairpin RNA (shRNA)-transduced HeLa cells further inhibited infection by N121K.…”
mentioning
confidence: 95%
“…Thus, it is tempting to speculate that the rate of uncoating may affect which nuclear import pathway HIV uses during infection. In contrast, A92E and G94D mutant viruses are impaired for infection in nondividing cells in a CypA-dependent manner (14,34). As only A92E mutant virus uncoats at a rate different from that of the wild-type virus, it seems unlikely that the inability of these mutants to infect nondividing cells is due to an altered rate of uncoating.…”
Section: Discussionmentioning
confidence: 82%
“…Because CypA can still bind the capsid, these mutants are proposed to alter the response of the virus to cellular CypA binding. In addition, these mutants are impaired for the ability of HIV to infect nondividing cells, indicating that they may have lost the ability to actively transport into the nucleus (14,34). In the CsA washout assay, A92E mutant virus uncoated faster than HIV-GFP with a significantly decreased half-life of uncoating (50 min) compared to the wild-type virus (90 min; Fig.…”
Section: Mutations In P24mentioning
confidence: 99%
“…Many reports have demonstrated that CA is the viral determinant for host factor recognition of the viral core (21,39,40,47,51,58,65) and that certain mutations in CA can specifically alter CypA recognition (7,21,23,27,49,55,58,61), but this is the first report that absence or certain mutations of IN can lead to changes in CypA recognition. How does IN mediate a change in host factor recognition of CA?…”
Section: Discussionmentioning
confidence: 88%